STRATEGI KOMUNIKASI TIM PRODUKSI ACARA MUSIC MORNING DI VIRGIN RADIO 99,9 FM DALAM MENINGKATKAN JUMLAH PENDENGAR - Yesianda, Alfa M; Liliyana, Liliyana; Indarsih, Mike (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research to know the communications strategy used by the production team in the virgin music morning 99,9 fm in increasing the number of radio listeners. Research questions submitted is how the communications strategy used by a team the production of a show music morning in the virgin radio 99.9 fm in increase the number of listener? A theory that used in this research is a theory control organization Describing a new approach and useful in communication organization in a relationship between organization to achieve an object. Methods used in this study was a methodology qualitative descriptive. the object of this research is the event of music morning responds by sending out in the virgin radio jakarta . Technique data collection done researchers is using a technique interviewing producer , successor program director , music director , announcers , marketing & amp; promotion . The researchers observation was directly involved in that is in the area of research locations palmerah to supervise the case , as well as the study literature available consisting of the books to be a source of research reading. The result showed that production team the music morning in the virgin jakarta radio applied the theory of control organization using all control to communicate directly between superior and subordinate. Researchers would give some advice , good advice theoretical and practical , as for advice that can be researchers talk about is maximize to promote taking advantage of all media promotion to the virgin radio jakarta especially the event music morning more widely known by the community.